The Independence of Notary in The Civil Partnership of Notary - Adha Dia Agustin (Rechtsidee, 2014)
The continued development of business in Indonesia, would make the greater role of the notary. The number of notaries and needed in each region in Indonesia gets greater. This rapid development, then coupled with the new policy. Previously, Peraturan Jabatan Notaris(PJN) prohibited Perserikatan, but since the establishment of Undang-Undang Jabatan Notaris (UUJN) has changed otherwise. Notary possible to make associations in a Civil Partnership. Even Peraturan Menteri Hukum dan HAM RI Nomor: M.HH.01.AH.02.12 Tahun 2010 tentang Persyaratan Menjalankan Jabatan Notaris Dalam Bentuk Perserikatan Perdata described the formation of the implementing regulations of the Civil Partnership. Is it true that Civil Partnership would make science benefit for junior notary and will facilitate the work of a Notary Or it would make large colonies notary who compete each other, so that the function of a notary public is no longer as state officials, but it called the company deed. This journal examines the Civil Partnership in Kitab Undang-Undang Hukum Perdata and would review the principle of the independence of the notary as set forth in Undang-Undang Jabatan Notaris. How To Cite: Agustin, A. (2014). The Independence of Notary in The Civil Partnership of Notary. Rechtsidee, 1(2), 131-146. doi:http://dx.doi.org/10.21070/jihr.v1i2.102